The determinants of IPO withdrawal - Evidence from Europe - Lucey, Brian; Vigne, Samuel (My University, 2019)
Why do companies not follow through with an IPO after filing for one? This question is investigated by examining common stock IPOs for the largest countries in Europe.We cover 80% of the Western European IPO market over the 2001-2015 period. We establish that the IPO phenomenon of withdrawal is a common feature of equity markets and identify key characteristics that influence the probability of withdrawal. Findings indicate that venture capital or private equity involvement, the presence of negative news, CEO duality, or the intent to retire debt increase the probability of IPO withdrawal. On the other hand, higher levels of corporate governance or trading volume decrease the probability of IPO withdrawal. We argue that imminent agency conflicts and the lack of appropriate control mechanisms can force a company to withdraw from the IPO
PUBLISHED
Keywords: Initial Public Offering; Europe; Withdrawal; Probit; International Development; International Integration; Culture